TALK-1 reduces delta-cell endoplasmic reticulum and cytoplasmic calcium levels limiting somatostatin secretion - Nicholas C. Vierra; Matthew T. Dickerson; Kelli L. Jordan; Prasanna K. Dadi; Ketaki A. Kadare; Molly K. Altman; Sarah C. Milian; David A. Jacobson (Molecular Metabolism, 2018)
Objective: Single-cell RNA sequencing studies have revealed that the type-2 diabetes associated two-pore domain K+ (K2P) channel TALK-1 is abundantly expressed in somatostatin-secreting δ-cells. However, a physiological role for TALK-1 in δ-cells remains unknown. We previously determined that in β-cells, K+ flux through endoplasmic reticulum (ER)-localized TALK-1 channels enhances ER Ca2+ leak, modulating Ca2+ handling and insulin secretion. As glucose amplification of islet somatostatin release relies on Ca2+-induced Ca2+ release (CICR) from the δ-cell ER, we investigated whether TALK-1 modulates δ-cell Ca2+ handling and somatostatin secretion. Methods: To define the functions of islet δ-cell TALK-1 channels, we generated control and TALK-1 channel-deficient (TALK-1 KO) mice expressing fluorescent reporters specifically in δ- and α-cells to facilitate cell type identification. Using immunofluorescence, patch clamp electrophysiology, Ca2+ imaging, and hormone secretion assays, we assessed how TALK-1 channel activity impacts δ- and α-cell function. Results: TALK-1 channels are expressed in both mouse and human δ-cells, where they modulate glucose-stimulated changes in cytosolic Ca2+ and somatostatin secretion. Measurement of cytosolic Ca2+ levels in response to membrane potential depolarization revealed enhanced CICR in TALK-1 KO δ-cells that could be abolished by depleting ER Ca2+ with sarco/endoplasmic reticulum Ca2+ ATPase (SERCA) inhibitors. Consistent with elevated somatostatin inhibitory tone, we observed significantly reduced glucagon secretion and α-cell Ca2+ oscillations in TALK-1 KO islets, and found that blockade of α-cell somatostatin signaling with a somatostatin receptor 2 (SSTR2) antagonist restored glucagon secretion in TALK-1 KO islets. Conclusions: These data indicate that TALK-1 reduces δ-cell cytosolic Ca2+ elevations and somatostatin release by limiting δ-cell CICR, modulating the intraislet paracrine signaling mechanisms that control glucagon secretion. Keywords: Two-pore domain K+ channel, KCNK16, Paracrine, Islet, Endoplasmic reticulum, Hormone secretion